CHARACTERISTICS OF PEDIATRIC NEUROGENIC BLADDER PATIENTS AT HASAN SADIKIN HOSPITAL PERIOD 2019 -2024 - Majid, Ghani Ikhsan; Sibarani, Jupiter (Indonesian Journal of Urology, 2025)
Objective: The purpose of this study was to characterize pediatric neurogenic bladder patients in order to recognize, treat, and avoid the related problems. Material & Methods: a retrospective study was conducted in the urology department's at Hasan Sadikin Hospital in Bandung, Indonesia. Data from pediatric neurogenic bladder patients who had urodynamic tests performed during the study period were evaluated. Results: Participants were predominantly female with 7 subjects (58.3%) while there were 5 male subjects (41.7%). The mean age of patients was 9.2 ± 5.44 years. Conservative management was the course of treatment for 10 patients (83.3%). The majority of this patient's bladder capacity—10 participants, or 83.33% of the total—have small capacities of less than 250. Seven patients (58.33%) had normal contractility, according to the bladder contractility index (BCI) inspection. Up to 7 participants (58.3%) had detrusor sphincter dyssynergia (DSD). Conclusion: Pediatric neurogenic bladder patients typically have small bladder capacities, according to urodynamic examination results. The most common symptoms that patients experience was those related to incontinence. The fundamental principle of treatment for children with neurogenic bladder is conservative therapy. Understanding the characteristics of neurogenic bladder patients and routinely carrying out urodynamic examinations allows early detection and appropriate treatment for this condition. Keywords: Pediatric, neurogenic bladder, urodynamic, incontinence.